Hajj Fund Investment: A Comparative Contemporary Fiqh Study on Maslahah and Public Policy Perspectives in Indonesia - Jaenal Aripin (MILRev: Metro Islamic Law Review, 2025)
This study investigates the investment of Indonesian Hajj funds in domestic infrastructure projects through a comparative fiqh approach, juxtaposing classical and contemporary Islamic legal perspectives on maslahah and its application within modern public policy frameworks. The central debate lies in a perceived conflict (ta‘arudl) between two types of public benefit: preserving the economic value of pilgrims' savings through investment and ensuring their spiritual rights and religious preparedness. Drawing upon classical jurisprudence (e.g., al-Ghazali, al-Shatibi), modern ijtihad, and official fatwas from Indonesian authorities (such as the DSN-MUI), the research critically examines how these positions interact with state policies enacted by the Badan Pengelola Keuangan Haji (BPKH). Employing a qualitative analytical method, the study analyzes legal texts, government regulations, and expert interviews to validate the coexistence of economic and spiritual maslahah. The findings reveal that the government’s dual role as wakil (authorized representative) and nazir (guardian of public interest) legitimizes proactive fund management under Islamic law. Sukuk-based investments, particularly when oriented toward infrastructure that supports public welfare, are found to be consistent with the objectives of maqasid al-shari‘ah, especially hifz al-mal (protection of wealth) and hifz al-din (preservation of religion). Moreover, the study identifies that transparent governance, informed consent, and adherence to Sharia-compliant instruments are critical prerequisites for ensuring ethical legitimacy. This study concludes that a harmonized approach between Islamic jurisprudence and Indonesian public policy can sustain Hajj financing while safeguarding pilgrims' rights and welfare.